Pengaruh Store Atmosphere dan Keragaman Produk terhadap Keputusan Pembelian (Studi pada Konsumen Susu Moeria Café di Kabupaten Kudus) - Veny Dwi Apriliani; Handojo Djoko Waloejo; Sudharto P Hadi (Universitas Diponegoro, 2022)
The increasing culinary industry in Indonesia is influenced by the emergence of many cafes. With changes in people's life style, cafes also be used as meeting places, completing tasks, or relaxing places. From there, the competition became increasingly fierce, so that cafe owners competed with each other to create attractive café designs and varied menus. One of the culinary places that feel the competition is Susu Moeria Café, which is one of the most well-known culinary places in Kudus Regency. The problem occurred because of a decline in sales at Susu Moeria Café which can be said to be quite drastic in 2020. Store atmosphere and product diversity are suspected as factors that can influence purchasing decisions. This study aims to determine the effect of store atmosphere and product diversity on purchasing decisions of Susu Moeria Cafe. This research’s type is explanatory research and the sampling method use non probability sampling and purposive sampling and accidental sampling methods. Data collection use the questionnaire. The samples are 100 respondents who are consumers of Susu Moeria Café. This research uses quantitative analysis with validity, reliability, correlation coefficient, determination coefficient, simple and multiple regression, significance of t and F test. The result of this study indicate that the variable store atmosphere and product diversity can simultaneously have a significant, strong, and positive influence on the purchasing decisions variable. Partially, the store atmosphere variable contributes on purchasing decisions of 39.8%, product diversity contributes of 52.5%. Simultaneously store atmosphere and product diversity contributes of 58.9% on purchasing decisions. It is recommended that Susu Moeria Café creates a good store atmosphere, and product development to increase product diversity which in can improve consumer purchasing decisions at Susu Moeria Café.